Peranan Majelis Taklim Dalam Penanaman Nilai-Nilai Islam Di Kecamatan Lubuklinggau Timur Ii Kota Lubuklinggau - Nurlila Kamsi (El-Ghiroh : Jurnal Studi Keislaman, 2016)
Islamic values ​​are applied to the congregation in the District Assembly taklim Lubuklinggau east II Lubuklinggau is faith, Islam, charity, piety, sincerity, trust, gratitude, patience, friendship, brotherhood, equality, fair, well thought, humble, the right appointment, gracefully, trustworthy, officer, thrift, and dermawan.Implementasi or actualizing values ​​of Islamic congregation taklim Assembly in District II East Lubuklinggau Lubuklinggau been done properly, the congregation has a strong faith and piety, with the faith of the pilgrims have a good life and gave birth to a sincere attitude in addition they also have good morals in dealing with fellow Muslims.